Treatment with prophylactic doses of ferrous sulphate in the fight against iron deficiency in children attended in basis health units - Torres, Marco A. A.; Sato, Kasue; Juliano, Yara; Queiroz, Suzana S. (Revista de Saúde Pública, 1994)
The efficacy of medical prophylaxis in the fight against iron deficiency anemia in 620 children aged from four to thirty-six months, attended in two health units of the municipality of S. Paulo, Brazil, was tested. First, the children's blood was tested for hemoglobin level and eletrophoresis. Then they received daily doses of iron sulphate in the form of drops, corresponding to 12 mg/ day of elementary iron, over a 30-day period. Afterwaeds, they were asked to return for re-evaluation. Twenty-five percent of children under 6 months presented hemoglobin levels under 11.0 g/dl. The highest occurrences of anemia were detected among children aged 9 to 11 months (49.5%) and in the age bracket between 12 and 23 months (50.4%). After the established period, only 37.4% of the children with anemia and 52.4% of children who did not present anaemia returned for further evaluation. Of the 299 evaluated, ony 157 (52.5%) had taken the medication correctly. Frequency of hemoglobin inferior to 9.5 g/dl dropped from 17.1% at the beginning to 8.1% at the end of the intervention. On the other hand, the percentage of children with hemoglobin above 12.0 g/ dl increased from 13.4% to 33.4%. Those chidren who took their iron supplements correctly registered a siginificantly higher drop in the number of cases of anemia than that observed in those who had not taken the supplement correctly. The great majority (80.3%) did not present any side effects of medication. It was concluded that medical prophylaxis, instead of proving to be efficient in the recovery of hemoglobin levels, presents serious hazards from the operation point of view including a low level of participation in the project on the part of mothers, resulting from the daily obligation to administer a medication to their chidren over a long period of time which can consequence generate saturation and forgetfulness.